The Breaking of Ochred Pebble Tools as Part of Funerary Ritual in the Arene Candide Epigravettian Cemetery. Issue 2 (18th January 2017) - Gravel-Miguel, Claudine; Riel-Salvatore, Julien; Maggi, Roberto; Martino, Gabriele; Barton, C. Michael
Abstract : We present the analysis of 29 human-transported limestone pebbles found during recent excavations (2009–11) in the Final Epigravettian levels at the Caverna delle Arene Candide, Italy. All pebbles are oblong, most bear traces of red ochre and many appear intentionally broken. Macroscopic analyses demonstrate morphological similarity with pebbles used as grave goods in the Final Epigravettian necropolis excavated at the site in the 1940s. Mediterranean beaches are the most plausible source for the pebbles, which were carefully selected for their specific shape. Microscopic observation of the pebbles' surfaces shows traces of ochre located on the edges and/or centres of most pebbles. A breakage experiment suggests that many pebbles were broken with intentional, direct blows to their centre. We propose that these pebbles were used to apply ochre ritually to the individuals buried at the site, and that some were subsequently ritually 'killed'. This study emphasizes the importance of studying artefacts that are often ignored due to their similarities to simple broken rocks. It also provides a method to study pebbles as a distinct artefact category, and shows that even broken parts should be studied to understand the story told by such objects in the context of prehistoric human social systems.